Associates between disease activity, biomarkers of bone turnover and habitual physical activity in patients with rheumatoid arthritis - Mthembu, Nonhlanhla Hlengiwe (My University, 2018)
Rheumatoid arthritis, the most common chronic inflammatory auto-immune joint disease, is a leading cause of chronic morbidity. People with rheumatoid arthritis often find activities of daily living difficult to perform due to pain. Together with low levels of physical activity, patients with rheumatoid arthritis have high levels of sedentary behaviour, the combination of which may contribute to poor bone health. Furthermore the chronic use of glucocorticoids, although effective for improving functional capacity, may also result in poor bone health. An active lifestyle however maintains functional capacity and can improve bone health in patients with rheumatoid arthritis. In spite of the benefits of an active lifestyle, patients who suffer from rheumatoid arthritis remain relatively inactive. Detailed and objectively measured physical activity patterns have not been well described in patients with rheumatoid arthritis in a longitudinal study. The value of such detailed information could contribute to informing targeted activity interventions in an effort to additionally improve the functional capacity in rheumatoid arthritis patients following standard treatment of their disease. There is also a paucity of literature that has examined the relationship between physical activity, sedentary behaviour and bone health in people with rheumatoid arthritis. This study aimed to determine: 1) changes in activity behaviours (defined here as physical activity and sedentary behaviour) and bone health following treatment and 2) whether there was a relationship between bone health (using biomarkers of bone turnover) and objectively measured patterns of physical activity and sedentary behaviour (using accelerometry) in newly diagnosed rheumatoid arthritis patients who are starting standard treatment therapy. Patients with rheumatoid arthritis were referred to a rheumatology clinic and upon diagnosis were invited to participate in the present study. Treatment-naïve patients (n=62) with rheumatoid arthritis who met inclusion criteria participated in this study. Routine therapy (methotrexate) was administered and titrated to target disease remission at 28 weeks after the onset of therapy. Assessments of self-report and clinician-reported patient function as well as activity behaviours were done before and 28 weeks after initiation of therapy. The health assessment questionnaire and the short-form 36-item health survey questionnaire were filled in by the patients with the guidance of a staff nurse. Habitual physical activity and sedentary behaviour were measured using an accelerometer. Biomarkers of bone turnover were assessed from a blood and urine sample. Patients showed a significant (p<0.0001) improvement in physical function measured using the questionnaires. The mean short-form 36-item health survey questionnaire score increased from 43.71 to 58.75 and the mean health assessment questionnaire scores decreased from 1.4 to 0.7 after 28 weeks of drug therapy, indicating that the disease-modifying anti-rheumatic drug treatment was successful in improving functional capacity. The accelerometry data showed no significant changes in physical activity and sedentary behaviour after 28 weeks of drug therapy. The participants spent the majority of their time in light intensity physical activity with durations of less than five minute bouts at a time and sedentary behaviour was mostly accumulated in bouts lasting 10-19 min at a time. There was no statistical significance in the change in objective measurements between participants who responded well, moderately and poorly to treatment according to disease assessment score. However, participants who had a good response to treatment increased their number of steps per day by almost 800, while those who had a moderate or poor response to treatment decreased their number of steps by approximately 1000 steps. There was a significant reduction in bone loss (mean Δ N-telopeptides of type I collagen =297.9-173.5 nmol) 28 weeks after treatment therapy. Overall objectively measured physical activity did not change significantly following diseasemodifying anti-rheumatic drug therapy in patients with rheumatoid arthritis. The functional capacity improvement reported using the short-form 36-item health survey questionnaire and the health assessment questionnaire was therefore not indicative of an improvement in activity behaviours as measured by accelerometers. The N-telopeptides of type I collagen and osteocalcin results suggest that disease-modifying anti-rheumatic drug therapy may help to protect the bone of rheumatoid arthritis patients from bone resorption however there is no relationship with levels of physical activity. The ability of only rheumatoid arthritis patients with a good response to treatment to increase their step count perhaps justifies the need to promote changes in lower intensity activity behaviours specifically. In those patients who do not respond well to treatment and who seemingly have difficulty in modifying their activity behaviours, focus on the lower intensity activities and sedentary behaviour may also be a more feasible target of behaviour modification. The results of this study together with future studies will be important in contributing to the development of activity behaviour guidelines aimed at improving the health of those with chronic inflammatory auto-immune joint disease.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine, 2018